Aircraft thermal management: Practices, technology, system architectures, future challenges, and opportunities. (1st January 2022) - van Heerden, A.S.J.; Judt, D.M.; Jafari, S.; Lawson, C.P.; Nikolaidis, T.; Bosak, D.
Abstract: The provision of adequate thermal management is becoming increasingly challenging on both military and civil aircraft. This is due to significant growth in the magnitude of onboard heat loads, but also because of their changing nature, such as the presence of more low-grade, high heat flux heat sources and the inability of some waste heat to be expelled as part of engine exhaust gases. The increase in the use of composites presents a further issue to address, as these materials are not as effective as metallic materials in transferring waste heat from the aircraft to the surrounding atmosphere. These thermal management challenges are so severe that they are becoming one of the major impediments to improving aircraft performance and efficiency. In this review, these challenges are expounded upon, along with possible solutions and opportunities from the literature. After introducing relevant factors from the ambient environment, the discussion of the challenges and opportunities is guided by a simple classification of the elements involved in thermal management systems. These elements comprise heat sources, heat acquisition mechanisms, thermal transport systems, heat rejection to sinks, and energy conversion and storage. Heat sources include both those from propulsion and airframe systems. Heat acquisition mechanisms are the means by which thermal energy is acquired from the sources. Thermal transport systems comprise cooling loops and thermodynamic cycles, along with their associated components and fluids, which move the heat from the source to the sinks over potentially large distances. The terminal aircraft heat sinks include atmospheric air, fuel, and the aircraft structure. In addition to the discussions on these different elements of thermal management systems, several topics of particular priority in aircraft thermal management research are deliberated upon in detail. These are thermal management for electrified propulsion aircraft, ultra-high bypass ratio geared turbofans, and high power airborne military systems; environmental control systems; power and thermal management systems; thermal management on supersonic transport aircraft; and novel modelling and simulation processes and tools for thermal management.